Hypertension In Children An Ignored Aspect Of Paediatric Health Care - SALEEMI MA SAGHIR A NAEEM S, IDREES H (Journal of Fatima Jinnah Medical University, 2018)
Objective: To estimate the presence of hypertension in children. Design: Descriptive study. Place & Duration of Study: The study was conducted at YWCA School at Queen’s Road Lahore from 1st of May 2010 to 31st of May 2010. Patients & Methods: All the children from class 1 to 10 underwent general physical examination including the blood pressure measurement. Hypertension was labeled when readings were greater than 95th centile of diastolic blood pressure. Results: There were 100 males and 62 females. Age range was 4-17 years. There were 12 (7%) children with hypertension, 9 (75%) males and 3 (25%) females respectively, out of which 3 males and 2 females were obese also. Conclusion: Hypertension is a health problem also in children